2017
DOI: 10.1149/07542.0099ecst
|View full text |Cite
|
Sign up to set email alerts
|

Ion Conduction of BaPrO3-δThin Film with Mixed Valence State for SOFC Anode Electrode

Abstract: The in-plane-oriented BaPrO 3-δ thin film with mixed valence states has been prepared on an Al 2 O 3 (0001) substrate by RF magnetron sputtering. The lattice constant decreases with increasing film thickness. The thin film has the mixed valence states of Pr 4+ and Pr 3+ . The ~168 nm thickness film with small lattice constant exhibits high electrical conductivity and low activation energy of 0.58 eV. The thin film at wet air shows hole-ion mixed conduction and proton conduction, which is required as anode elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…26,27 BaPrO 3− δ with various B-site acceptor dopants such as Gd, Yb, and Y was reported as a potential triple conductor (holes, oxide ions, protons), 28–30 and thin films of BaPrO 3− δ that supported both protonic and electronic conductivity apparently hosted multivalent Pr 3+/4+ which contributed to oxygen vacancy formation. 31–33 In prior work, we also demonstrated that BPY can undergo oxygen exchange, where it has an anomalously low redox coefficient of chemical expansion, 34 which may aid chemo-mechanical stability.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…26,27 BaPrO 3− δ with various B-site acceptor dopants such as Gd, Yb, and Y was reported as a potential triple conductor (holes, oxide ions, protons), 28–30 and thin films of BaPrO 3− δ that supported both protonic and electronic conductivity apparently hosted multivalent Pr 3+/4+ which contributed to oxygen vacancy formation. 31–33 In prior work, we also demonstrated that BPY can undergo oxygen exchange, where it has an anomalously low redox coefficient of chemical expansion, 34 which may aid chemo-mechanical stability.…”
Section: Introductionmentioning
confidence: 72%
“…The film Bragg diffraction peak positions are reasonably matched with those of BaPrO 3− δ thin films in the literature. 32,37 For the BCFZY thin film on sapphire, (110), (211), (220), and (311) Bragg reflections were observed, suggesting a polycrystalline film without strongly preferred orientation. The peak positions are also similar with those of a BCFZY thin film grown by PLD in literature.…”
Section: Resultsmentioning
confidence: 99%
“…No contribution of the grain boundary was observed in the Cole-Cole plots. Therefore, the conductivities reflect the bulk resistance(7). These conductivities exhibit the thermal activation-type behaviors.…”
mentioning
confidence: 99%